THE MUSIC OF AFRICA by J.H. Kwabena Nketia, (Gollancz) London, 1975. Copyright 1974 by W.W. Norton Inc. - Blacking, John; Jones, A. M.; Pantaleoni, Hewitt (International Library of African Music, 1975)
pages: 155-160
Keywords: African Music